Central Executive Dysfunction and Deferred Prefrontal Processing in Veterans With Gulf War Illness. (May 2014) - Hubbard, Nicholas A.; Hutchison, Joanna L.; Motes, Michael A.; Shokri-Kojori, Ehsan; Bennett, Ilana J.; Brigante, Ryan M.; Haley, Robert W.; Rypma, Bart
Gulf War Illness is associated with toxic exposure to cholinergic-disruptive chemicals. The cholinergic system has been shown to mediate the central executive of working memory. In the current work, we propose that impairment of the cholinergic system in Gulf War Illness patients (GWIPs) leads to behavioral and neural deficits of the central executive of working memory. A large sample of GWIPs and matched control participants underwent functional MRI during a varied-load working memory task. Compared with matched control participants, GWIPs showed a greater decline in performance as working memory demand increased. Functional imaging results suggested that GWIPs evinced separate processing strategies, deferring prefrontal cortex activity from encoding to retrieval for high-demand conditions. Greater activity during high-demand encoding predicted greater working memory performance. Behavioral data suggest that working memory executive strategies are impaired in GWIPs. Functional data further support this hypothesis and suggest that GWIPs use less effective strategies during high-demand working memory.